Waste disposal of small wine and liquor agroindustry into tributaries of the Soturno and Jacuí rivers, Rio Grande do Sul, Brazil. - Krolow,Daniela (Universidad de Tarapacá. Facultad de Ciencias Agronómicas, 2021)
ABSTRACT The reduction of water quality typically starts in small streams and rivers; tributaries interconnected to major rivers. In this regard, this study aimed to investigate waste disposal of small wine and liquor agribusinesses by monitoring the water quality of two streams, tributaries of the Soturno and Jacuí rivers, located in the Quarta Colônia region the state of Rio Grande do Sul (RS), Brazil. We began monitoring water quality in July 2008 and continued uninterruptedly until May 2009. We collected water samples at three different locations (source, upstream, and downstream) in triplicate, totaling 162 samples. We investigated 24 variables that makeup chemical, physical and biological parameters of water quality. With the results, we concluded that the diffuse sources of pollution in the "Liquor stream" are associated with wastewater of small agribusinesses and nearby residences, in contrast, the source of the "Wine stream" showed the most chemical changes in water quality, and whose diffuse sources of pollution are more associated with agricultural activity than the small agribusinesses activity. The variables of chemical and biological oxygen demand, dissolved oxygen, total iron, total manganese, and total phosphorus presented values higher than those of Class II waters in both streams. Therefore, small agribusinesses need to adequately dispose of the waste in order to meet existing legislation comprehensively.